SUBDUCTION OF SEDIMENTS AND LEVELS OF 10BE IN LAVAS OF THE KURILE ISLANDS AND KAMCHATKA - Tsvetkov A.A.; Gladkov N.G.; Volynets O.N. (My University, 1989)
One of the important problems in studying island-arc igneous activity is that of its sources. A key problem is that of demonstrating subduction of an oceanic plate beneath an island arc and the involvement of its component rocks, primary sediments, in island-arc magmatism. The calculations indicate that the highest fraction of sedimentary material in the magma chambers producing present-day lavas of the Kurile volcanoes in less than 4 percent and that for the Kamchatka volcanoes it is less than 2 percent. These results confirm the conclusion that we reached earlier from a study of the isotopic composition of Nd and Sr and the distribution of rare earths, that small but real quantities of sedimentary material were involved in magma generation in the vicinity of the Kurile island arc. Authors data represent the first direct confirmation of the mechanism of subduction in this segment of the Asia-Pacific transition zone and must be borne in mind in geodynamic reconstructions.